Acquisition of L2 morphology by adult language learners. (July 2019) - Kimppa, Lilli; Shtyrov, Yury; Hut, Suzanne C.A.; Hedlund, Laura; Leminen, Miika; Leminen, Alina
Abstract: Learning a new language requires the acquisition of morphological units that enable the fluent use of words in different grammatical contexts. While accumulating research has elucidated the neural processing of native morphology, much less is known about how second-language (L2) learners acquire and process morphology in their L2. To address this question, we presented native speakers as well as beginning and advanced learners of Finnish with spoken (1) derived words, (2) inflected words, (3) novel derivations (novel combinations of existing stem + suffix), and (4) pseudo-suffixed words (existing stem + pseudo-suffix) in a passive listening EEG experiment. An early (60 msec after suffix deviation point) positive ERP response showed no difference between inflections and derivations, suggesting similar early parsing of these complex words. At 130 msec, derivations elicited a lexical ERP pattern of full-form memory-trace activation, present in the L2 beginners and advanced speakers to different degrees, implying a shift from lexical processing to more dual parsing and lexical activation of the complex forms with increasing proficiency. Pseudo-suffixed words produced a syntactic pattern in a later, 170–240 msec time-window, exhibiting enhanced ERPs compared to well-formed inflections, indicating second-pass syntactic parsing. Overall, the L2 learners demonstrated a gradual effect of proficiency towards L1-like responses. Advanced L2 learners seem to have developed memory traces for derivations and their neurolinguistic system is capable of early automatic parsing. This suggests that advanced learners have already developed sensitivity to morphological information, while such knowledge is weak in beginners. Discrepancies in ERP dynamics and topographies indicate partially differing recruitment of the language network in L1 and L2. In beginners, response differences between existing and novel morphology were scarce, implying that representations for complex forms are not yet well-established. The results suggest successful development of brain mechanisms for automatic processing of L2 morphology, capable of gradually attaining L1-like functionality with increasing proficiency.